Communicating Maritime Spatial Planning: The MSP Challenge approach. (October 2021) - Abspoel, Lodewijk; Mayer, Igor; Keijser, Xander; Warmelink, Harald; Fairgrieve, Rhona; Ripken, Malena; Abramic, Andrej; Kannen, Andreas; Cormier, Roland; Kidd, Sue
Abstract: The MSP Challenge uses game technology and role-play to support communication and learning for Marine/Maritime Spatial Planning. Since 2011, a role-playing game, a board game and a digital interactive simulation platform have been developed. The MSP Challenge editions have been used in workshops, conferences, education, as well as for real life stakeholder engagement. The authors give an overview of the development of the MSP Challenge and reflect on the value of the approach as an engaging and 'fun' tool for building mutual understanding and communicating MSP.